Ayurvedic management of acne vulgaris - Abhishek Upadhyay; Hari Khanal; Ram Kishor Joshi (Wolters Kluwer Medknow Publications, 2021)
Introduction: Acne vulgaris has always been one of the most burning problems of the young population. Acne vulgaris like presentation in Ayurveda has been described as Shalmali thorn like eruptions on the face due to vitiation of Kapha, Vata, and Rakta under the heading of Mukhadushika. Very less scientific data is available depicting the effect of Ayurvedic intervention in such cases. Main Clinical Finding: Present case reports a 26 years old female having multiple acne for the past 6 months. She had papules and pustule with itching, pain, and blackish spots on cheeks. Diagnosis: Condition was diagnosed as Acne vulgaris (Ayurvedic diagnosis - Pitta-Kapha dominant Tridoshika Mukhadushika). Interventions: The patient was treated with Kaishor Guggulu, Raktaprasadakahima, and the local application of Terminalia arjuna powder mixed with honey daily for 1 month. Outcome: The patient had relief in all the symptoms after 15 days of treatment with no new eruptions. Complete remission of the disease was observed after 1 month of treatment with the improved skin condition. Conclusion: This case study demonstrates the potential and usefulness of Ayurveda in the management of acne vulgaris.